2017
DOI: 10.1007/s13197-017-2789-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of broiler chicken meat quality and factors affecting them: a review

Abstract: Broiler production at mass level has already been achieved and now emphasis is being laid on increasing meat quality by altering various characteristics of broiler meat. Appearance, texture, juiciness, wateriness, firmness, tenderness, odor and flavor are the most important and perceptible meat features that influence the initial and final quality judgment by consumers before and after purchasing a meat product. The quantifiable properties of meat such as water holding capacity, shear force, drip loss, cook lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
394
4
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(430 citation statements)
references
References 78 publications
(82 reference statements)
16
394
4
16
Order By: Relevance
“…According to Reitznerová et al [92], lipid oxidation in meat can be monitored through the value of thiobarbituric acid reactive substances (TBARS). Many studies have reported that broilers raised at high temperatures increased TBARS in plasma, organs and carcass [71,72]. For this reason, these authors can conclude that the presented modified TBARS spectrophotometric method is suitable for monitoring the lipid oxidation processes in meat samples [92].…”
Section: Lipid and Protein Oxidationmentioning
confidence: 78%
“…According to Reitznerová et al [92], lipid oxidation in meat can be monitored through the value of thiobarbituric acid reactive substances (TBARS). Many studies have reported that broilers raised at high temperatures increased TBARS in plasma, organs and carcass [71,72]. For this reason, these authors can conclude that the presented modified TBARS spectrophotometric method is suitable for monitoring the lipid oxidation processes in meat samples [92].…”
Section: Lipid and Protein Oxidationmentioning
confidence: 78%
“…According to Mir et al [72], light scattering affects meat lightness (L*) in a fashion inverse to that caused by heme pigment concentration, having a minimal effect on meat redness (a*) and yellowness (b*). It could be argued that appearance is the most important quality attribute of cooked or raw poultry meat because consumers associate it with the product's freshness, and they may decide whether or not to buy the product based solely on their opinion of its attractiveness [72]. In general, meat with a higher proportion of red fibers has a higher concentration of myoglobin, which is related to the predominance of aerobic (oxidative) metabolism, and a red color (greater than L*) and darker (lower L*) [35].…”
Section: Colormentioning
confidence: 99%
“…PSE meat is the result of accelerated post-mortem glycolysis, which results in a rapid post-mortem decline in pH while carcass temperatures are still high. Among the environmental factors to induce occurrence of PSE meat, ante-mortem stress, heat stress at the end of the growth or pre-slaughter phase and methods of stunning in the slaughterhouse seem to play the main role [72,73]. Van de Perre et al [68] reported that in the summer, the risk of PSE in pigs is almost double the risk in winter, as these animals are sensitive to high temperatures.…”
Section: Colormentioning
confidence: 99%
“…Nowadays, the industrial technology of broiler bird production broadens requirements for supplying birds with various biologically active substances [1][2][3]. One of the most important elements of the intensive technology of producing eggs and poultry meat is organization for full and balanced feeding, which is the basis of the most complete manifestation of the productivity genetic potential, the efficient use of nutrients from the ration, the high natural resistance of the organism, and the product quality [4,5]. Preventive measures in the context of modern poultry production should organically fit the process.…”
Section: Introductionmentioning
confidence: 99%